(untitled) - Engel, Heino (Rutland, Vt., 1985)
Heino Engel studied architecture in Germany immediately following the end of World War II, then traveled through Egypt and Arabia, spent more than a year in India, Burma, Malaysia, and Thailand, before arriving in Japan. There, in his own words, he "realized that the Japanese house is as invaluable an experience for the contemporary architect as are the ancient Acropolis of Athens in Greece and the modern high-rise office towers of the United States." He remained in Japan for three years, concentrating on the study of the Japanese house, people, life, language, and culture, and also becoming a member of the Architectural Institute of Japan.
Keywords: House construction,Architecture, domestic; Japan,Japan